2008
DOI: 10.1108/09555340810913520
|View full text |Cite
|
Sign up to set email alerts
|

Theory and practice across disciplines: implications for the field of management

Abstract: Purpose -The aim of this paper is to contribute to the debate about the existence and nature of a "gap" between theory and practice in management. Design/methodology/approach -The putative theory/practice "gap" in management is investigated by examining the theory/practice debate in three cognate fields -economics, nursing and marketing. Findings -The relationship between theory and practice is actively debated in all three of the fields. In economics, criticism has been directed at the implicit ontological as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Practitioners often see little, if any, relevance of management research to them (e.g. Gioia and Corley, 2002;Brennan, 2008;Fendt et al, 2008;Kuusela et al, 2014;Banks et al, 2016) despite efforts to the contrary. For example, Arlbjørn et al, (2008) emphasize the importance of researchbased education, especially within the Danish context, where the Government has enshrined this principle in law.…”
Section: Research Relevancementioning
confidence: 99%
“…Practitioners often see little, if any, relevance of management research to them (e.g. Gioia and Corley, 2002;Brennan, 2008;Fendt et al, 2008;Kuusela et al, 2014;Banks et al, 2016) despite efforts to the contrary. For example, Arlbjørn et al, (2008) emphasize the importance of researchbased education, especially within the Danish context, where the Government has enshrined this principle in law.…”
Section: Research Relevancementioning
confidence: 99%
“…Nurses, for example, are encouraged by their employers . Managers insist on evidence, question the authority of evidence, and provide access to a good range of information sources, Evidence-based practice is high on organisational agendas, and is linked to innovation, creativity and learning (Brennan 2008) . Evidence-based practice can also be promoted by knowledge intermediaries, who may be members of, or have a strong relationship with, clinical and other decision-making teams .…”
Section: Evidence-based Culturesmentioning
confidence: 99%
“…There is well-established recognition of the importance of marketing research as a process and a collection of techniques through which managers and marketers gather intelligence about their customers, competitors and marketplaces . In addition, a number of authors have discussed what they describe as the academic-practitioner divide (Brennan & Ankers 2004) or the research-practice gap (Brennan 2008) or have demonstrated the difference between practitioner knowledge and academic knowledge (Gambetti & Graffigna 2010) . Yet, to date, there has been no explicit consideration of the applicability of the concepts of evidence-based practice or evidence-based management in the marketing area .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moscardo and Norris (2005) have made an effort to bridge academic practitioner gap in event management by training students with market oriented assignments. As Brennan (2008) debated on the solutions of theory practice gap across the disciplines of economics, nursing and marketing.…”
Section: Literature Reviewmentioning
confidence: 99%